Influencing factors on continuance intention to adopt mobile payment: the mediating role of user satisfaction - Kun, Vannak; Hong, Soun; Rady , Chhun (Southeast Asian Journal of Service Management, 2026)
This study investigates the factors influencing user satisfaction and continuance intention toward mobile payment applications in Cambodia, an emerging leader in ASEAN digitalization. Utilizing the Extended Expectation-Confirmation Model in Information Technology (EECM-IT) as a framework, the research examines the impact of perceived usefulness, ease of use, service quality, credibility, compatibility, subjective norms, and perceived risk on long-term user behavior. Data were collected through a structured survey of 470 active mobile payment users in Cambodia and analyzed using Covariance-Based Structural Equation Modeling (CB-SEM). The results indicate that perceived usefulness, ease of use, service quality, credibility, and subjective norms significantly and positively influence user satisfaction. Notably, perceived usefulness emerged as the strongest predictor of continuance intention. While perceived ease of use was critical for initial satisfaction, its direct influence on continued usage diminished as users became proficient with the technology. User satisfaction was confirmed as a vital mediator, bridging the gap between technological attributes and habitual loyalty. Interestingly, perceived risk and compatibility did not show a significant impact on satisfaction in this specific context. These findings provide critical insights for financial institutions and policymakers aiming to foster a sustainable cashless ecosystem in Cambodia.